2021
DOI: 10.1016/j.cppeds.2021.100949
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric behavioral telehealth in the age of COVID-19: Brief evidence review and practice considerations

Abstract: Considerable efforts over the last decade have been placed on harnessing technology to improve access to behavioral health services. These efforts have exponentially risen since the outbreak of the Coronavirus disease 2019 (COVID-19), which has prompted a move to novel systems of care, largely based on telehealth delivery. This article aims to provide a broad review of evidence for telehealth assessment and treatment of externalizing disorders and internalizing disorders in children and discuss practice consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 98 publications
2
53
0
1
Order By: Relevance
“…Clinicians broadly reported that telehealth can be a good option for many clients in that it is convenient, generally acceptable, and may even provide surprising benefits such as increased creativity and collaboration, increased parental involvement, and an ability for clinicians to gain a more intimate understanding of their clients’ home environment (ie, more ecological validity), which can provide clinically important information that would not otherwise be available. These benefits are supported by other studies [ 50 , 51 ], and provide promising implications regarding the potential for the longstanding use of telehealth for clients who prefer this modality. Positive views about telehealth are also reflected in our quantitative data, which show relatively favorable ratings of telehealth, especially when considering the quick pivot and lack of preparation.…”
Section: Discussionsupporting
confidence: 71%
“…Clinicians broadly reported that telehealth can be a good option for many clients in that it is convenient, generally acceptable, and may even provide surprising benefits such as increased creativity and collaboration, increased parental involvement, and an ability for clinicians to gain a more intimate understanding of their clients’ home environment (ie, more ecological validity), which can provide clinically important information that would not otherwise be available. These benefits are supported by other studies [ 50 , 51 ], and provide promising implications regarding the potential for the longstanding use of telehealth for clients who prefer this modality. Positive views about telehealth are also reflected in our quantitative data, which show relatively favorable ratings of telehealth, especially when considering the quick pivot and lack of preparation.…”
Section: Discussionsupporting
confidence: 71%
“… 33 Other studies also found acceptable concordance with guideline-based care for the assessment and treatment of children with behavior health and externalizing disorders, including attention and disruptive behavior problems. 34 Importantly, telemedicine can also be used to facilitate COVID-19 screening, diagnosis, and monitoring from home. 35 …”
Section: Introductionmentioning
confidence: 99%
“…The American Academy of Pediatrics,120 Philippine Pediatric Society,121 American Academy of Child and Adolescent Psychiatry,122 and the American Psychiatric Association123 recommend routine and crisis telemedicine and teleconsultation, and the International Paediatric Association124 currently recommends these during the pandemic. Telepsychiatry is widely used and effective125; however, access is inequitable,120124125126 and it may not be effective for many young children who require interactive play therapies.…”
Section: How Can You Manage Children’s and Adolescents’ Mental Health And Wellbeing?mentioning
confidence: 99%